Blindness in Africa: present situation and future needs. Issue 8 (1st August 2001) - Lewallen, Susan; Courtright, Paul
Abstract : AIM: To review the prevalence and causes of blindness in sub-Saharan Africa, the existing services and limitations, and the Vision 2020 goals for the future. METHODS: Methodologically sound population based surveys published in the past 20 years are reviewed and results for prevalence and causes of blindness are tabulated. The current resources and needs according to recent publications and international working groups are described. CONCLUSIONS: Blindness prevalence rates vary widely but the evidence suggests that approximately 1% of Africans are blind. The major cause is cataract; trachoma and glaucoma are also important causes of blindness. The bulk of blindness in the region is preventable or curable. Efforts should focus on eye problems which are universally present and for which there are cost effective remedies, such as cataract and refractive problems and on those problems which occur focally and can be prevented by primary healthcare measures, such as trachoma, onchocerciasis, and vitamin A deficiency. Major development of staffing levels, infrastructure, and community programmes will be necessary to achieve Vision 2020 goals.